Managing risks in collaborative governance environment: A literature review - Adzariat, Nuriat; Pratama, Muhammad Agi; Leksmanawati, Widya (Institute of Computer Science (IOCS), 2023)
The post-covid is still as challenging as covid-19 era. Private and governmental organizations were required to overcome difficulties in carrying out operational activities and discovering solutions. Hence, it is crucial to utilize comprehensive approaches to ensure the continuous execution of essential public interest activities, even in limited situations. Collaborative governance is widely defined as the methods and structures for formulating policy decisions and overseeing administration in ways that serve the public interest, going beyond the limitations of public institutions. Due to the primary aim of collaborative governance significantly influencing public interests, effective and efficient results become highly crucial. Risk management on collaboration risk identification is needed to ensure accountability among public sector officials. While institutionalism studies have received considerable attention, there is a limited focus on the significance of risk management in sustaining collaborative outcomes. The purpose of this study was to review systematically the existing research addressing collaboration-related risks and exploring potential solutions. This research examines journal articles released within the past decade, covering the period from 2013 to 2023. Nevertheless, the study continues to rely on certain foundational theories from the past. This study will enable the effective resolution of the implemented solution in conducting collaborative governance as effectively and efficiently as possible which could be useful for future researchers, policymakers, and related stakeholders